Can Teamwork and High-Volume Experience Overcome Challenges of Lymphadenectomy in Morbidly Obese Patients (Body Mass Index of 40 kg/m2 or Greater) with Endometrial Cancer?: A Cohort Study of Robotics and Laparotomy and Review of Literature. Issue 5 (1st June 2018) - Fornalik, Hubert; Zore, Temeka; Fornalik, Nicole; Foster, Todd; Katschke, Adrian; Wright, Gary
Abstract : Objective: This study aimed to compare surgical outcomes and the adequacy of surgical staging in morbidly obese women with a body mass index (BMI) of 40 kg/m 2 or greater who underwent robotic surgery or laparotomy for the staging of endometrioid-type endometrial cancer. Methods: This is a retrospective cohort study of patients who underwent surgical staging between May 2011 and June 2014. Patients' demographics, surgical outcomes, intraoperative and postoperative complications, and pathological outcomes were compared. Results: Seventy-six morbidly obese patients underwent robotic surgery, and 35 underwent laparotomy for surgical staging. Robotic surgery was associated with more lymph nodes collected with increasing BMI ( P < 0.001) and decreased chances for postoperative respiratory failure and intensive care unit admissions ( P = 0.03). Despite a desire to comprehensively stage all patients, we performed successful pelvic and paraaortic lymphadenectomy in 96% versus 89% ( P = 0.2) and 75% versus 60% ( P = 0.12) of robotic versus laparotomy patients, respectively. In the robotic group, with median BMI of 47 kg/m 2, no conversions to laparotomy occurred. The robotic group experienced less blood loss and a shorter length of hospital stay than the laparotomy group; however, the surgeries were longer. Conclusions: In a high-volume center, a high rate of comprehensive surgical staging can be achieved in patients with BMI of 40 kg/m 2 or greater either by laparotomy or robotic approach. In our experience, robotic surgery in morbidly obese patients is associated with better quality staging of endometrial cancer. With a comprehensive approach, a professional bedside assistant, use of a monopolar cautery hook, and our protocol of treating morbidly obese patients, robotic surgeries can be safely performed in the vast majority of patients with a BMI of 40 kg/m 2 or greater, with lymph node counts being similar to nonobese patients, and with conversions to laparotomy reduced to a minimum.